2022
DOI: 10.1155/2022/3797548
|View full text |Cite|
|
Sign up to set email alerts
|

The Path of Digital Government and University Asset Intelligence Value-Added Service Driven by Block Chain Technology

Abstract: At present, the government and universities mainly adopted the centralized management mode in the sharing of asset digital resources, which not only had low work efficiency, but also cannot make full use of resources. Block chain technology played an important role in enterprise asset data resource data sharing, but there was less research on asset data sharing services applied to digital government and universities. Therefore, this paper proposed the research on the path of government and university asset val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Engineering has retracted the article titled "Te Path of Digital Government and University Asset Intelligence Value-Added Service Driven by Block Chain Technology" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Journal Of Electrical and Computermentioning
confidence: 99%
“…Engineering has retracted the article titled "Te Path of Digital Government and University Asset Intelligence Value-Added Service Driven by Block Chain Technology" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Journal Of Electrical and Computermentioning
confidence: 99%